IMPROVING STUDENTS™ READING COMPREHENSION THROUGH DIRECTED READING THINKING ACTIVITY - Barus, Ricky Drimarcha (TRANSFORM: Journal of English Language Teaching and Learning, 2012)
This study aims at improving students™ reading comprehension through Directed Reading Thinking Activity. The objective of this study is to find out whether students™ reading comprehension achievement improved if they are taught by using Directed Reading Thinking Activity. In this study, classroom action research is conducted. The sample is one class of the second year students of SMA Katolik 1 Kabanjahe. The total number of the students is 40 students. The data are acquired from tests, observation sheet and questionnaire sheet. The students™ score mean is improved in every test. The mean of the second cycle (73.35) is higher than that in the first cycle (59.38) and in the pre-test (43.28). The observation sheet and questionnaire sheet show that the students™ reading comprehension achievement is improved. These findings indicate that applying Directed Reading Thinking Activity improved students™ reading comprehension. Key Words: Directed Reading Thinking Activity, reading comprehension